ANALISIS PENGARUH PRODUCT QUALITY, PRICE, DAN PROMOTION TERHADAP PURCHASE INTENTION MOBIL (Studi Pada Konsumen di Showroom SAM Mobil Sumenep) - Ahmad Faqih Rahman; Agus Widarko; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research was done in Sumenep Car’ SAM Showroom. The kind of research used is quantitative research. The purpose of this research is to know the influence of Quality Product, Price, and Promotion to Purchase Intention. Free variable is used Product Quality, Price, and Promotion, while the bunch variable is Purchase Intention. Sample used of this research is forty five respondent is form consumer from Sumenep Car’ SAM Showroom. Data collect technique use questionnaire. Analisys method used instrumen test, classic assumption test, unequel linier regression analysis, F test, dan t-test. Used soft equipment computer SPSS 16.0. the result of this research show that Product Quality have effect to Purchase Intention. Price have effect to Purchase Intention. And Promotion not effect to Purchase Intention. Product Quality, Price, and Promotion have simultanious effect to Purchase Intention.Keywords : Product Quality, Price, Promotion, Purchase Intention.